Proceedings of the XXXI Brazilian Symposium on Software Engineering 2017
DOI: 10.1145/3131151.3131168
|View full text |Cite
|
Sign up to set email alerts
|

How Do Software Developers Identify Design Problems?

Abstract: When a software design decision has a negative impact on one or more quality attributes, we call it a design problem. For example, the Fat Interface problem indicates that an interface exposes non-cohesive services. Thus, clients and implementations of this interface may have to handle with services that they are not interested. A design problem such as this hampers the extensibility and maintainability of a software system. As illustrated by the example, a single design problem often a ects several elements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Sousa et al have shown that developers often combine multiple symptoms to identify design problems [41]. However, they did not observe how that combination took place.…”
Section: Symptom Analysis In Symptom Analysis Developers Choosementioning
confidence: 98%
See 1 more Smart Citation
“…Sousa et al have shown that developers often combine multiple symptoms to identify design problems [41]. However, they did not observe how that combination took place.…”
Section: Symptom Analysis In Symptom Analysis Developers Choosementioning
confidence: 98%
“…As far as we are concerned, Sousa et al is the only study that has proposed to explain how developers identify design problems [41]. However, they fell short of framing their results as a theory.…”
Section: Related Workmentioning
confidence: 99%
“…According to Sousa et al, 26 a software design problem occurs when a software design decision has a negative impact on one or more quality attributes of the software. A design problem impacts on some of the key properties (such as extensibility and maintainability, robustness, comprehensibility, and performance) of a software system.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Other studies have focused on investigating the identification of design problems from the perspective of developers as well [47,48]. Sousa et al [47] conducted a qualitative study to investigate how developers identify design problems in practice. In their study, the authors observed the actions that developers apply to identify design problems.…”
Section: Other Approaches To Identify Design Problemsmentioning
confidence: 99%